2021
DOI: 10.2340/00015555-3898
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Pretreatment Peripheral Neutrophil Count and Neutrophil-to-lymphocyte Ratio in Primary Cutaneous Angiosarcoma

Abstract: Systemic inflammatory response markers, including neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and monocyte-to-lymphocyte ratio, are useful prognostic factors for various malignant tumours. The aim of this study was to investigate the clinical relevance of these markers in primary cutaneous angiosarcoma. Twenty-six patients were retrospectively divided into 2 groups according to pretreatment peripheral blood cell counts or systemic inflammatory response marker levels; overall survival and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Two small retrospective studies from Japan have reported on the prognostic role of hematological biomarkers in primary cutaneous angiosarcomas. In a retrospective study of 26 patients with primary cutaneous angiosarcoma, a high NLR (>2.4) was an independent prognostic factor for shorter overall survival (HR = 5.04, 95%CI: 1.26–20.1; p = 0.022) [ 59 ]. Another, case–control study reported a statistically significant difference in NLR and PLR values between 17 patients with angiosarcoma of the face and scalp (ASFS) and 56 healthy matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…Two small retrospective studies from Japan have reported on the prognostic role of hematological biomarkers in primary cutaneous angiosarcomas. In a retrospective study of 26 patients with primary cutaneous angiosarcoma, a high NLR (>2.4) was an independent prognostic factor for shorter overall survival (HR = 5.04, 95%CI: 1.26–20.1; p = 0.022) [ 59 ]. Another, case–control study reported a statistically significant difference in NLR and PLR values between 17 patients with angiosarcoma of the face and scalp (ASFS) and 56 healthy matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective analysis of psoriasis patients in China, Egypt, and Turkey, NLR and PLR were also found to be elevated and correlated with disease severity [35][36][37]. The combination of NLR and PLR can predict adverse events in patients with acute myocardial infarction and prognosis of malignant tumors [38,39]. There is no consistent trend as to which marker, NLR or PLR, has a stronger association with disease severity or predicts systemic inflammation more accurately.…”
Section: Discussionmentioning
confidence: 99%